ANALISIS PERAN TENAGA PENDIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI 01 ULAK KARANG SELATAN KOTA PADANG - Astri, Yuyun; Azkiya, Hidayati; Morelent, Yetty; Yulisna, Risa (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2025)
This study aims to analyze the role of educators in improving the quality of education at SDN 01 Ulak Karang, Padang City. The theory used refers to Hasbullah (2017), who states that educators must act as mentors, inspirers, and motivators for their students. Educators are expected to possess strong pedagogical, social, professional, and personal competencies to support the achievement of quality education. This study employs a qualitative approach with data collection techniques including interviews, questionnaires, and documentation. The research subjects consist of the school principal and teachers in phases A, B, and C. The results show that educators have performed their roles well in enhancing the quality of education. Based on interviews, 80% of the school principal and teachers stated that educators have played an optimal role, while 20% mentioned that there are still infrastructure limitations. These limitations include the lack of fans in phase B (grade 4) and power supply constraints due to the use of projectors in all classrooms in phase C (grade 5). The questionnaire results indicate that 80% of respondents strongly agree, 20% agree, and none expressed disagreement or uncertainty. The documentation collected supports the interview and questionnaire data, with 80% of the documents showing that educators actively contribute to improving education quality, while 20% highlight challenges related to infrastructure. In conclusion, educators at SDN 01 Ulak Karang have played an active role in enhancing education quality. However, infrastructure challenges remain and require further attention to ensure an optimal learning process.. Keywords : Role of educators, education quality